Impacto de diferentes métodos de avaliação da obesidade abdominal após síndromes coronarianas agudas - Nunes, Caroline N. [UNESP]; Minicucci, Minicucci F. [UNESP]; Farah, Elaine [UNESP]; Fusco, Danieliso [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Paiva, Sérgio A. R. [UNESP]; Zornoff, Leonardo A. M. [UNESP] (Sociedade Brasileira de Cardiologia, 2014)
Background: Abdominal obesity is an important cardiovascular risk factor. Therefore, identifying the best method for measuring waist circumference (WC) is a priority. Objective: To evaluate the eight methods of measuring WC in patients with acute coronary syndrome (ACS) as a predictor of cardiovascular complications during hospitalization. Methods: Prospective study of patients with ACS. The measurement of WC was performed by eight known methods: midpoint between the last rib and the iliac crest (1), point of minimum circumference (2); immediately above the iliac crest (3), umbilicus (4), one inch above the umbilicus (5), one centimeter above the umbilicus (6), smallest rib and (7) the point of greatest circumference around the waist (8). Complications included: angina, arrhythmia, heart failure, cardiogenic shock, hypotension, pericarditis and death. Logistic regression tests were used for predictive factors. Results: A total of 55 patients were evaluated. During the hospitalization period, which corresponded on average to seven days, 37 (67%) patients had complications, with the exception of death, which was not observed in any of the cases. Of these complications, the only one that was associated with WC was angina, and with every cm of WC increase, the risk for angina increased from 7.5 to 9.9%, depending on the measurement site. It is noteworthy the fact that there was no difference between the different methods of measuring WC as a predictor of angina. Conclusion: The eight methods of measuring WC are also predictors of recurrent angina after acute coronary syndromes. Key words: Evaluation; Acute Coronary Syndrome; Abdominal Circumference
Impact of different obesity assessment methods after acute coronary syndromes
Keywords: Evaluation; Acute coronary syndrome; Abdominal circumference; Avaliação; Síndrome coronariana aguda; Circunferência abdominal